Game Theoretical Approaches for Optimizing Multi-Carrier Half-Duplex Successive Relaying Based Cooperative NOMA - H. Horler; B. Rastegari; S. X. Ng (IEEE Open Journal of Vehicular Technology)
In this work, a novel power auctioneers network is proposed to allow the sharing of resources from Edge Users in exchange for performance gains using either the Cooperative Non-Orthogonal Multiple Access (C-NOMA) or Half-Duplex Successive Relaying based C-NOMA protocol. The latter is presented as a novel method of using two relays in C-NOMA through successive relaying to overcome the multiplexing loss in traditional C-NOMA of the far user. This system exploits two matching-based algorithms based on game theory, namely Conventional Distributed Algorithm (CDA) and Pragmatic Distributed Algorithm (PDA), to handle the challenge of user pairing and power allocation in multi-carrier networks. These approaches use distributed methods to perform tasks on user devices to remove the strain on the base station's resources. Monte Carlo simulations demonstrate that the addition of these games to a wireless network provides a significant performance gain compared to traditional orthogonal multiple access methods, unoptimised C-NOMA, and the Distributed Matching Algorithm. Specifically, the cooperative game of PDA is shown to perform better in several scenarios, including when the subcarrier assignment was fixed and when EUs could occupy multiple subcarriers to enhance their throughput.